MITOS-MITOS DALAM KEPERCAYAAN MASYARAKAT - Nurbaiti Masni; Sovia Astari; Ryan Satria Antoni; Desyandri; Muhammadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
What myths exist in society and what values are contained in society’s myths. The method used in this research is a qualitative descriptive method. In other words, to explain or classify myths and consider the values contained in myths in society. The next research approach is a structural approach, based on visible facts and not numbers. The data collection techniques used in this research were recording, observation and interviews. The data processing technique then carries out the steps of copying these myths with the recording results, turning them into meaningful stories and representations, then analyzing the values and interpreting the data to draw conclusions. The results of this research show that oral form of mythology is a literary work that must be preserved so that it does not become extinct. Thesemyths contain many benefits in human life through moral messages and religious teachings that can be applied in people’s daily lives.